Digital Intensive English untuk Meningkatkan Kompetensi Speaking Mahasiswa PPL–KKN Internasional - Astuti, Widi; Charneidy, Muhammad Avryzal (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
The Digital Intensive English Programme is designed to improve the English speaking skills of prospective PPL–KKN international participants through digital-based learning. This programme is conducted online for one month (17 July–15 August 2025) and involves 10 students from the PAI and PBA Study Programmes at STAI Masjid Syuhada Yogyakarta. The method used is Communicative Language Teaching (CLT), which is implemented in synchronous sessions for targeted oral communication practice. The main results show an improvement in students' speaking skills and confidence, with an average increase of 30% in fluency and pronunciation based on a comparison of pre-test and post-test results. In addition to linguistic achievements, this programme also strengthened digital literacy and reflective, collaborative, and adaptive attitudes in learning. These findings confirm the programme's contribution as an effective digital-based community service model to prepare students for international communication needs and support the internationalisation agenda of Islamic higher education institutions